Transmitter-based inverse filters for reducing MAI and ISI in CDMA-TDD downlink. - Georgoulis, S.L (IEEE Transactions on wireless communications)
Inverse filters (INVF) are introduced as a new transmitter-based precoding scheme for the code-division multiple access-time division duplex (TDD) downlink. Multiple access interference and intersymbol interference are significantly reduced while the mobile station's structure is reduced to a filter matched to the user's spreading code. The method assumes knowledge of the channel at the transmitter which is feasible under TDD. The new algorithm uses a minimum mean-squared error criterion with power constraint. When compared with existing schemes, INVF increase the system performance while maintaining a low computational cost. The theoretical analysis is supported with simulation results. Analytical bit-error rates for any precoding algorithm is also calculated.